Performance of a novel household solar heating thermostatic biogas system. (5th March 2016) - Feng, Rong; Li, Jinping; Dong, Ti; Li, Xiuzhen
Highlights: A novel over-ground household solar heating thermostatic biogas system was developed. Full-scale field experiments on biogas production characteristics were conducted. The biogas produced can satisfy the cooking fuel demands of farmers even in winter in the cold regions. The dynamic payback period of the system with 5.66 years was obtained. Abstract: Household biogas plays a critical role in energy supplying and environmental protection in Chinese rural areas. A novel over-ground household solar heating thermostatic biogas system was developed in this study to improve the biogas production rates in winter in cold regions of China. Full-scale field experiments on the biogas production characteristics of the system in seven batches process for more than a year and a semi-continuous process experiment for nearly four months during winter were conducted in cold regions of China, together with the amount of daily heat consumed by the digester in the semi-continuous process. The economic feasibility of the system was also evaluated. The average biogas production rates of 0.63, 0.68, 0.44, 0.64, 0.93, 1.09 and 1.08 m 3 /(m 3 slurry⋅d) at T 80 were determined in seven batches. In the semi-continuous process experiment, four daily biogas production peaks of 1.39, 1.60, 2.39, and 2.15 m 3 emerged on days 35, 56, 74 and 112 respectively. The total biogas yield during the test was 110.71 m 3, with a methane content of 54.74%. The biogas produced in the semi-continuous process satisfied the cooking fuel demands of three to five farmers. The biogas production rate increased rapidly when the amount of time consumed during slurry temperature after reloading was small. The heat consumed by the digester was 15 MJ/d–30 MJ/d during the worst time of the year. The NPV and DDP of the system were 7708 yuan and 5.66 years respectively. Suggestions based on the experimental results were proposed for the efficient use of biomass resources in rural areas and for the improvement of biogas production reliability. The proposed novel household biogas system can play a significant role in using biomass resources to satisfy farmers' cooking fuel demands in cold rural regions.